The Influence of Reading Interests, Vocabulary Mastery and Critical Thinking on Reading Comprehension in Elementary School Students - Fahrurrozi; Dewi, Ratna Sari; Hasanah, Uswatun; Wahyudi, Apri (International Journal of Psychosocial Rehabilitation, 2020)
Vocabulary mastery is a number of words that a person know both productively which using words, and receptively that used to understand the meaning of words in language activities, especially reading. The purpose of this research is to find out whether there is an influence of reading interests, vocabulary mastery, and critical thinking on reading comprehension in the sixth grade students of elementary schools in South Jakarta. This research used quantitative method by utilizing path analysis statistical test tool. Path Analysis is used to test the influence of intervening variables. The findings of this study indicate that there is an influence between reading interest, vocabulary mastery and critical thinking on reading comprehension of elementary school students. Vocabulary mastery significantly improve students’ reading comprehension. Reading comprehension is also influenced by students’ critical thinking. By having critical thinking, students will be better in reading comprehension.